Effects of Vitamin E and/or selenium nanoparticles on organ histology, hemato-biochemical parameters, immunity, gene expression, and growth performance in Nile tilapia challenged with Enterococcus faecalis - Fatima S. Alaryani; Najah M. Albaqami; Samia Elbahnaswy; Gehad E. Elshopakey; Layla A. Almutairi; Basma M. Hendam; Marwa S. Khattab; Ola Hasan Abd El Megeed; Roshmon Thomas Mathew; Zulhisyam Abdul Kari; Yasmin M. Abd El-Aziz; Moaheda E.H. Eissa; et al. (Aquaculture Reports)
A two-month feeding experiment was conducted to assess the impact of dietary selenium nanoparticles (SeNPs), sodium selenite (Se), and vitamin E (Vit E) on the growth performance, hematology profile, innate immune response, histomorphology of the liver, intestine, and gills, as well as gene expression in Nile tilapia (Oreochromis niloticus) challenged with the pathogenic bacteria Enterococcus faecalis. A total of 360 fish were allocated into six experimental groups and fed diets containing 1 mg/kg of SeNPs (SeNPs), 1 mg /kg of sodium selenite (Se), 100 mg/kg of Vit E (VE), SeNPs+ Vit E, Se+ Vit E and a control group (CON) without any additives. The results showed that SeNPs and SeNPs+ Vit E diets significantly improved the growth performance (final body weight, feed intake, fish biomass, specific growth rate, and feed conversion ratio) and blood parameters compared to the other groups (P<0.05). Liver enzymes (AST, ALT, and ALP) were significantly decreased, while immune responses were enhanced in the serum of fish in the SeNPs and SeNPs+ Vit E groups before and after the E. faecalis challenge. The expression of pro-inflammatory genes (TNF-α and IL-8) was significantly lower in the SeNPs and SeNPs+ Vit E groups, both before and after the E. faecalis challenge, compared to the other groups (P<0.05). Nile tilapia fed the control diet and challenged with E. faecalis exhibited a high mortality rate (85 %), whereas mortality was significantly lower in fish fed supplemental SeNPs (45 %) and SeNPs+ Vit E (40 %). Histological examination also revealed improvements in liver, intestine, and gill functions in Nile tilapia fed SeNPs+ Vit E. These results suggest that dietary SeNPs, either alone or in combination with Vit E, can significantly enhance fish performance, innate immune response, liver function enzymes, and reduce the expression of pro-inflammatory genes in Nile tilapia. They can also mitigate the pathological effects caused by the E. faecalis challenge.